Pola pengeluaran dan gaya hidup penduduk muda kelas menengah: Studi empiris perkotaan di Jabodetabek - Ningrum, Vanda; Putri, Intan Adhi Perdana; Ekaputri, Andini Desita (Jurnal Kependudukan Indonesia, 2014)
Youth occupies a great segment of population in metropolitan cities. Since the era of industrialization in 1980s, many of these youth are categorised as middle class group. Their expenditure patterns and lifestyle have a strong influence to the country economics as well as urban planning regulations. This paper aims to analyse the behaviour of youth who perceived themselves as young middle class population based on their expenditure pattern and lifestyle. The research surveyed those whose age spans from 18 to 35 years old, reside and work in the urban cities, namely Jakarta, Bogor, Depok, Tangerang, and Bekasi. Results of the survey showed, there is a different pattern of consumption between young middle class population who are single and married. Single individuals tend to spend their monthly income for food culinary as their first priority. In the other hand, young marriage couple tends to spend their income for paying their house or car loans. Although, in average, young middle class frequently visit shopping malls, their expenditure on entertainment is not their top priority from total expenditure per month. Their main reason visiting malls is to seek for a convenient environment compared to spending their income as a mean to reach a certain social status. Given the imbalance between growing number of malls (supply) and lack of spending (demand), moratorium of malls can be one regulations issued by the government to provide alternative public areas or Open Green Areas (RTH) such as parks.